Intellectual Property and Genetic Resources, Traditional Knowledge and Traditional Cultural Expressions - World Intellectual Property Organization (Geneva, Switzerland WIPO, 2020)
General information on the interface between intellectual property (IP) and traditional knowledge (TK), traditional cultural expressions (TCEs), and genetic resources (GRs). It briefly addresses the most important questions that arise when considering the role that IP principles and systems can play in protecting TK and TCEs from misappropriation, and in generating and equitably sharing benefits from their commercialization, and the role of IP in access to and benefit sharing in GRs.General information on the interface between intellectual property (IP) and traditional knowledge (TK), traditional cultural expressions (TCEs), and genetic resources (GRs). It briefly addresses the most important questions that arise when considering the role that IP principles and systems can play in protecting TK and TCEs from misappropriation, and in generating and equitably sharing benefits from their commercialization, and the role of IP in access to and benefit sharing in GRs. Información general sobre la interfaz entre la propiedad intelectual (PI) y los conocimientos tradicionales (TK), las expresiones culturales tradicionales (ECT) y los recursos genéticos (RG). Aborda brevemente las cuestiones más importantes que surgen al considerar el papel que pueden desempeñar los principios y sistemas de PI en la protección de los CC.TT. y las ECT frente a la apropiación indebida, y en la generación y distribución equitativa de los beneficios de su comercialización, y el papel de la PI en el acceso y la distribución de beneficios. en RR.GG. Información general sobre la interfaz entre la propiedad intelectual (PI) y los conocimientos tradicionales (TK), las expresiones culturales tradicionales (ECT) y los recursos genéticos (RR.GG.). Aborda brevemente las cuestiones más importantes que surgen al considerar el papel que pueden desempeñar los principios y sistemas de PI en la protección de los CC.TT. y las ECT frente a la apropiación indebida, y en la generación y distribución equitativa de los beneficios de su comercialización, y el papel de la PI en el acceso y la distribución de beneficios. en GR.
List of boxes -- Why use this booklet? -- Background to the need for the Protection of Traditional Knowledge, Traditional Cultural Expressions, and Genetic Resources -- The Issue in a Nutshell -- What are Traditional Knowledge, Traditional Cultural Expressions, and Genetic Resources? -- Who are the holders of Traditional Knowledge and Traditional Cultural Expressions? -- What is the objective of Protection? -- Existing conventional intellectual property systems -- Adaptation of Existing intellectual property -- Sui Generis Systems -- The Intergovernmental Committee -- Projects and activities: the practical work of WIPO -- Indigenous participation in WIPO.
Keywords: GENETIC -- TRADITIONS -- CULTUR -- PROPERTY INTELLECTUAL